The „Twin Crisis”: Suez and Budapest, 1956 - Kecskés, Gusztáv D. (Acta Scientiarum Socialium, 2016)
The "Twin Crisis": Suez and Budapest, 1956.This essay will summarize what we know about the connection between the two parallel crises. Based on archival materials and publications derived from them, it seems that there was not only a temporal coincidence between the Suez and Hungarian crises during the Fall of 1956. Although the two series of events stem from totally different causes, the two crises influenced and affected one another. Therefore we can offer the following responses to our basic questions: although the confusing situation in Europe and the Soviet Union’s occupation must have come up at the Sèvres meeting of the British-French-Israeli allies on October 22-24 in preparation for the Suez action, this question did not influence their changing of the date of attack. Raising the issue, the British and French tried to reassure the Israelis who feared a Soviet military counter-attack. On the other hand, the Suez action could not have affected the final outcome of the debate in the Kremlin since they had been discussing Hungary’s fate for days. However, it may have had a secondary effect on its decisions.
Keywords: Cold War history; international relations; Suez crisis; 1956 Hungarian revolution; Near East